Towards a mobile system with a new wearable device and an AI application for walking and running activities - Alvim, Patrick B. N.; Silva, Jonathan C. F. da; Amorim, Vicente J. P.; Lazaroni, Pedro S. O.; Silva, Mateus Coelho; Oliveira, Ricardo A. R. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2023: Anais do L Seminário Integrado de Software e HardwareDO - 10.5753/semish.2023.230082, 2023)
Recognizing human activities from mobile applications is a challenging task due to the complexity of the context. Several healthcare applications consider wearable devices, including in the orthopedic area. Considering this context, we proposed a novel mobile application that can recognize walking activities with data collected by new wearable sensors on the user’s leg. The wearable system collects the data, which is processed using Edge AI. Then, we propose to present the generated information as a digital twin considering the user’s movements based on the sensor data. For this work, the wearable device and AI movement classification are operational, while the mobile application is still in development.